Detecting hybridization between sister species of Terebratulina (Brachiopoda, Cancellothyridoidea) in the North Atlantic: morphology versus molecules - Carsten Lüter (Nature Portfolio, 2017)
Abstract Investigating samples of the cancellothyridid brachiopod Terebratulina collected during the IceAGE (Me85/3) expedition of RV METEOR at the continental shelf around Iceland with both morphometrical and molecular methods, we were for the first time able to detect a hybridization event between brachiopod sister species, which are thought to have separated 60 MYA. Terebratulina retusa and T. septentrionalis can clearly be distinguished on the basis of consistent species-specific molecular signatures in both mitochondrial and nuclear markers, whereas morphometrical analyses proved to be less reliable for species determination than previously thought. Two out of 28 specimens were identified as offspring of a one-way hybridization event between T. retusa eggs and T. septentrionalis sperm. Whereas the fossil record of Terebratulina in the North Atlantic region is too fragmentary to reconstruct the history of the hybridization event, the different life history traits of the two species and current oceanographic conditions around Iceland offer plausible explanations for the occurrence of crossbreeds in this common brachiopod genus.